Experimental demonstration of a variable-rate LDPC code with adaptive low-power decoding for next-generation optical networks - Morero, Damian A. (2016)
Fil: Morero, Damian A. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales. Instituto de Estudios Avanzados en Ingeniería y Tecnología; Argentina.